Analisis Indikator komposit Indeks Pembangunan Manusia dan Kemiskinan terhadap Pertumbuhan Ekonomi di Provinsi Banten - Maria Bernadette Nani Ariani; Indri Arrafi Juliannisa (Universitas Islam Nahdlatul Ulama Jepara, 2021)
This study aimed to determine the influence and factors that cause low school year expectancy, life expectancy, purchasing power, and the number of poor people on economic growth in Banten Province. This study uses data from 2014 to 2019. The method used in this study is the panel data analysis method with theapproach Random Effect Model. The result of panel data analysis shows that the variable of school duration expectancy, life expectancy, purchasing power, and the number of poor people simultaneously influence economic growth in Banten Province. Partially, the variable expectation of school years and people's purchasing power has a significant positive effect on economic growth in Banten Province, the variable life expectancy has a significant positive effect on economic growth in Banten Province and the number of poor people has a significant negative effect on economic growth in Banten Province.